EFFECT OF DIFFERENT SOURCES AND LEVELS OF SULPHUR ALONG WITH FOLIAR SPRAY OF MICRONUTRIENTS ON GROWTH YIELD AND NUTRIENT UPTAKE BY SAFFLOWER (CARTHAMUS TINCTORIUS L.). - Magodia, Heena A.; Jagasia, Pooja. V.; Kale, Archana. P. (ShodhKosh: Journal of Visual and Performing Arts, 2024)
A field experiment conducted during the rabi season of January 2024 in Narayangaon, Maharashtra, India investigated the effects of various sulphur sources combined with micronutrient spray on the growth and yield of safflower (Carthamus tinctorius L.). A Randomized Block Design for eight treatments in four replications each having either elemental sulphur or gypsum in combination with NPK and micronutrient spray (Cu 1.0%, Zn 3.0%, Mn 1.0%, Fe 2.5%, B 0.5%, Mo 0.1%) were tested. The treatment (T4) combination of 45 kg/ha elemental sulphur with NPK and micronutrient produced significantly higher plant height (110.64 cm), number of branches (22.33), yield (1483.9 kg/ha), and chlorophyll content (1.08 mg/g). While the dry weight per plant (39.2gm), 1000-seed weight (56.19 g), oil content (28.86%), and protein content (15.24%), were exhibited at par with (T7). These treatments (T4) indicating a direct correlation between higher elemental sulphur application rates and improved plant growth, yield and seed quality. These findings indicate that optimizing balanced fertilization strategies that include appropriate sulphur and other micronutrient applications can substantially improve safflower productivity in sulphur-deficient regions.